The neglected part of early embryonic development: maternal protein degradation - Toralova, Tereza; Kinterova, Veronika; Chmelikova, Eva; Kanka, Jiri (Cellular and molecular life sciences, 2020)
The degradation of maternally provided molecules is a very important process during early embryogenesis. However, the vast majority of studies deals with mRNA degradation and protein degradation is only a very little explored process yet. The aim of this article was to summarize current knowledge about the protein degradation during embryogenesis of mammals. In addition to resuming of known data concerning mammalian embryogenesis, we tried to fill the gaps in knowledge by comparison with facts known about protein degradation in early embryos of non-mammalian species. Maternal protein degradation seems to be driven by very strict rules in terms of specificity and timing. The degradation of some maternal proteins is certainly necessary for the normal course of embryonic genome activation (EGA) and several concrete proteins that need to be degraded before major EGA have been already found. Nevertheless, the most important period seems to take place even before preimplantation development-during oocyte maturation. The defects arisen during this period seems to be later irreparable.
Keywords: Autophagy; oocyty; Animals; Humans; embryonální vývoj; Proteasome system; Gene Expression Regulation, Developmental; Ubiquitin; vývojová regulace genové exprese; Ubiquitin ligase; embryo savčí; genom; Embryonic genome activation; Embryonic Development; Proteins; zvířata; proteiny; Embryo, Mammalian; Oocytes; embryo nesavčí; lidé; Embryo, Nonmammalian; Genome; Maternal to zygotic transition